Comparing the Efficacy of Instrument-Assisted Soft Tissue Mobilization and Massage Therapy in Alleviating Gastrocnemius Muscle Pain in 800-Meter Runners - Kurniawan, Muhammad Dwi; Deasy Virka Sari; Ragil Aidil Fitriasari Addini; Aditya Hans Suwignjo (Physiotherapy and Physical Rehabilitation Journal, 2024)
This study investigated the effects of Instrument-Assisted Soft Tissue Mobilization (IASTM) and massage therapy on reducing gastrocnemius muscle pain in 800-meter runners experiencing delayed onset muscle soreness (DOMS). The primary objective was to compare the effectiveness of these two interventions in alleviating muscle pain. We conducted a quasi-experimental study with 40 athletes randomly assigned to either the IASTM or massage therapy group. Pain levels were measured using the Visual Analog Scale (VAS) before and after a 4-week intervention period. Results indicated that while neither intervention showed a statistically significant difference (p > 0.05), massage therapy provided a greater average pain reduction (4.0) compared to IASTM (3.5). This suggests that massage therapy may be slightly more effective for managing DOMS. Our research contributes to the field of sports medicine by providing evidence on the comparative effectiveness of IASTM and massage therapy, offering insights that can help optimize recovery strategies for athletes